A new human topoisomerase III that interacts with SGS1 protein. - Ng, S W (1999)
Eukaryotic DNA topoisomerase III was first identified by studying the hyper-recombination and slow growth phenotypes of yeast mutants. Topoisomerase III interacts with DNA helicase SGS1 and the two proteins are involved in DNA recombination, cellular aging and maintenance of genome stability. A human homolog of topoisomerase III has previously been identified. Here we report the identification of cDNAs and the determination of gene structure for a second human topoisomerase III gene. This novel gene expresses three alternatively spliced transcripts, which encode gene products different in the putative DNA-binding C-termini. The largest gene product of the novel topoisomerase III was expressed and shown to interact with SGS1 protein and partially rescue the slow growth defect of a yeast topoisomerase III mutant. The presence of more than one human topoisomerase III is reminiscent of mammalian topoisomerase II, which has two genetically distinct isoforms with different expression patterns and probably different functions in mammalian cells.